Como se cria um vilão? Rumores e intrigas entre teatro e literatura do melodrama à dramaturgia brasileira no século XIX - Ludwig, Paula Fernanda (2012)
This work aims to understand the consolidation of the villain as a stereotypical character, representative of questions related to conception of social, cultural and historical values, according to a collective imagination. For tihs, it seeks to support the comparative analysis of two works in which we can see the configuration of this character one, linked to a theater type, very popular, the melodrama, and other linked to Brazilian dramaturgy in the nineteenth century. This approach favors the observation of relevant aspects about the development of theater in Brazil, at a time when there was an accentuated movement towards the establishment of a national culture. In this context, there was a conflict between the aim of producing works of literary quality, according to foreign standards (mostly European) and scenic exercise. However, in this period, there was a predominance of representations of popular forms, like the melodrama, acclaimed by general public. Its success stimulated influence of its features in writing of the national works, encouraged the exploration of aspects like the utilization of villains characters and the relationship between written text and elements of the scenic spectacle, approaching theatre and literature with the composition of spectacular texts, based on the use of rubrics. Therefore, in this study, we present a show that this happened in practice and suggest its income in the characterization of the Brazilian literature.